Double-layer hydrogel for wound repair and infection monitoring as well as preparation method and application of double-layer hydrogel

By developing a double-layer hydrogel, the infection monitoring is performed using metal ion-crosslinked upper hydrogel, and the release of mulberry extracts is accelerated by the Schiff alkali reaction lower hydrogel, the existing hydrogel in infection is solved. Deficiencies in monitoring and treatment have achieved versatile and efficient wound healing.

CN119431837APending Publication Date: 2025-02-14XIEHE HOSPITAL ATTACHED TO TONGJI MEDICAL COLLEGE HUAZHONG SCI & TECH UNIV

Patent Information

Application Number
CN202411567623.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing hydrogels have defects in wound infection monitoring and treatment, such as lack of real-time monitoring functions, uncontrollable drug release rates, and lack of hemostasis and anti-tension properties.

Method used

Develop a double-layer hydrogel, the upper hydrogel is based on metal ion crosslinking, which can change the color under different pH conditions for infection monitoring; the lower hydrogel is based on a crosslinking network of Schiff base reaction, under acidic conditions Accelerate release of mulberry extract to promote wound healing.

Benefits of technology

Real-time monitoring and treatment of wound infection is realized, and has multifunctional features such as shape adaptability, tissue adhesion, hemostasis, antibacterial, pH-responsive biodegradation, etc., to meet the needs of full-process wound treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431837A_ABST
    Figure CN119431837A_ABST
Patent Text Reader

Abstract

The invention discloses double-layer hydrogel for wound repair and infection monitoring as well as a preparation method and application of the double-layer hydrogel, and belongs to the technical field of biological medicines. The preparation method comprises the following steps: (1) firstly, preparing an aldehyde dextran-mulberry extract solution; (2) preparing a chitosan quaternary ammonium salt-mulberry extract solution; (3) mixing and dissolving sodium alginate, aldehyde dextran and mulberry extract in a PBS (Phosphate Buffer Solution), so as to obtain an upper-layer hydrogel pre-polymerization solution; (4) mixing the aldehyde dextran-mulberry extract solution with the chitosan quaternary ammonium salt-mulberry extract solution, so as to prepare a lower layer hydrogel; and (5) adding the upper-layer hydrogel prepolymerization liquid above the lower-layer hydrogel, and spraying a metal cation salt solution to enable the upper-layer hydrogel to be fully crosslinked, thereby obtaining the crosslinked hydrogel with a double-layer structure. The double-layer hydrogel for wound repair and infection monitoring, prepared by the invention, has good adhesion, tensile property, antibacterial property and hemostatic property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedicine technology, and in particular relates to a double-layer hydrogel for wound repair and infection monitoring, and a preparation method and application thereof. Background Art

[0002] After the skin structure is damaged, the human body will quickly start the repair process. With the participation of various functional cells, it will go through the hemostasis period, inflammation period, proliferation period and remodeling period, and finally restore the integrity of the skin. As an organ in direct contact with the external environment, the skin faces a high risk of infection after being damaged. Once the infection occurs, it will lead to wound angiogenesis disorders, excessive inflammation, epithelial formation disorders, and ultimately lead to non-healing of the wound. Hydrogels have received widespread attention in wound management due to their adjustable mechanical properties, suitable drug delivery properties, good hygroscopicity and biocompatibility. At present, many hydrogels focus on wound treatment, such as promotion of cell function and antibacterial, but lack real-time monitoring of wound status. Considering that bacterial infection may occur at various stages of wound healing, it is crucial to develop hydrogels with bacterial detection and promotion of wound repair.

[0003] Bacteria in wounds decompose organic matter and produce acid, causing the pH value of infected wounds to drop. Therefore, monitoring the pH value of the wound area is considered to be an effective method to reflect the infection status. Anthocyanin is a natural flavonoid found in plants such as mulberry. The molecular form of anthocyanin aglycones in aqueous solution changes with the pH value, and these changes lead to significant differences in the color of anthocyanin solutions. It is worth noting that anthocyanins also have antioxidant and anti-inflammatory biological effects and are a potential tissue promoter. Invention patent application 202310888577.X discloses "a wound dressing and its preparation method". The AgNPs / anthocyanin modified chitosan hydrogel dressing disclosed in the patent application realizes wound pH monitoring through anthocyanins, and AgNPs are used for antibacterial purposes, but AgNPs are potentially toxic to cells related to tissue repair. In addition, the biological effect of anthocyanins is dose-dependent. This method of anthocyanin grafting limits the effective release of anthocyanins, and the therapeutic function of anthocyanins themselves may be affected. Invention patent application 202110956537.5 discloses "a coordination compound, its preparation method and application". This patent application uses electrospinning technology to load anthocyanin-metal ion coordination compounds on scaffold materials, aiming to monitor and treat wound infections. However, the release rate of the coordination compound from the scaffold is uncontrollable, and the scaffold itself lacks hemostatic and tensile properties. Therefore, there is an urgent need to develop multifunctional wound dressings to match the requirements of wound infection monitoring and treatment. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a double-layer hydrogel for wound repair and infection monitoring, and a preparation method and application thereof. The hydrogel dressing is a double-layer hydrogel loaded with mulberry extract, wherein the upper and lower hydrogel dressings have different physical and chemical properties. The upper hydrogel relies on metal ion cross-linking, has a stable structure under different pH conditions, and can change color in response to pH changes in infected wounds, so it can be used for wound infection monitoring. The lower hydrogel is a cross-linked network based on Schiff base reaction, which can accelerate the release of mulberry extract under acidic conditions for wound treatment. In general, the hydrogel dressing has the ability of shape-adaptive gelation, tissue adhesion, hemostasis, antibacterial, pH-responsive biodegradation, infection monitoring and promotion of tissue repair, meeting the needs of full-course wound treatment.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a double-layer hydrogel for wound repair and infection monitoring, the preparation method comprising the following steps:

[0007] (1) dissolving 0.3-0.5 g of aldehyde-deoxyglucan and 45-55 mg of mulberry extract in 8-12 mL of PBS buffer at pH 7.4 to prepare an aldehyde-deoxyglucan-mulberry extract solution;

[0008] (2) dissolving 0.3-0.5 g of chitosan quaternary ammonium salt and 45-55 mg of mulberry extract in 8-12 mL of PBS buffer at a pH of 7.4 to form a chitosan quaternary ammonium salt-mulberry extract solution;

[0009] (3) 0.3-0.4 g of sodium alginate, 0.3-0.5 g of aldehyded dextran and 45-55 mg of mulberry extract were mixed and dissolved in 8-12 mL of PBS buffer with a pH of 7.4 to serve as the upper hydrogel prepolymer solution;

[0010] (4) mixing the aldehyde-deoxyglucan-mulberry extract solution and the chitosan quaternary ammonium salt-mulberry extract solution in a volume ratio of 1-2:1-2, and allowing to stand for a cross-linking reaction to form a lower layer of hydrogel;

[0011] (5) Add the upper hydrogel prepolymer solution on top of the lower hydrogel, spray the metal cation salt solution, and let it stand to allow the upper hydrogel to be fully cross-linked, thereby obtaining a cross-linked hydrogel AlgOdx-ME@QcsOdx-ME with a double-layer structure.

[0012] Preferably, in step (1), the amount of aldehyded dextran used is 0.4 g, and the amount of mulberry extract used is 50 mg.

[0013] More preferably, in the step (2), the amount of chitosan quaternary ammonium salt used is 0.4 g, and the amount of mulberry extract used is 50 mg.

[0014] More preferably, in the step (3), the amount of sodium alginate used is 0.35 g, the amount of aldehyded dextran used is 0.4 g, and the amount of mulberry extract used is 50 mg.

[0015] More preferably, the metal cation salt solution in step (5) is a CaCl2 solution. Other metal cation solutions that can induce cross-linking of sodium alginate hydrogel are also applicable, such as salt solutions of metals such as copper and zinc.

[0016] More preferably, the volume of the PBS buffer in steps (1)-(3) is 10 mL.

[0017] The invention also provides a double-layer hydrogel prepared by the preparation method.

[0018] The present invention also provides the use of the double-layer hydrogel in preparing wound repair and infection monitoring products.

[0019] The principle of the present invention is as follows: the present invention constructs a double-layer hydrogel, the upper and lower layers of the double-layer hydrogel are loaded with mulberry extract rich in anthocyanins, and the two layers of hydrogel are cross-linked by Schiff base reaction. The upper layer hydrogel is based on a sodium alginate hydrogel network cross-linked by metal cations, which contains aldehyde-modified polysaccharide molecules. The upper layer hydrogel network is stable under acidic conditions, and the pH-responsive color-changing characteristics of anthocyanins can be used to realize wound infection monitoring based on pH changes. The lower layer hydrogel is a dynamic hydrogel network based on Schiff base reaction containing quaternary ammonium salt groups, which has good adhesion, tensile properties, antibacterial properties and hemostatic properties. Under the acidic pH value of infection, the lower layer hydrogel can be rapidly degraded, and the mulberry extract is released faster, inhibiting the polarization of macrophages M1 and promoting the polarization of macrophages M2, thereby exerting a strong anti-inflammatory effect, thereby promoting wound healing.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The smart hydrogel for wound repair and infection monitoring proposed in the present invention has good adhesion, tensile properties, antibacterial properties and hemostatic properties. The upper layer of hydrogel can show different colors according to the pH of the wound, which is used to judge wound infection. The lower layer of hydrogel can degrade in response to the acidic microenvironment. This pH-responsive degradation mode accelerates the release of drugs in the hydrogel and improves the utilization rate of the drugs. After being applied to infected wounds, the lower layer of hydrogel in the present invention quickly releases mulberry extract rich in anthocyanins, thereby accelerating the transition from the inflammatory phase to the proliferation phase of the wound, and ultimately accelerating wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 These are the characterization results of the AlgOdx-ME@QcsOdx-ME hydrogel in Example 2, wherein A is the SEM image of the upper AlgOdx-ME hydrogel and the lower QcsOdx-ME hydrogel of the AlgOdx-ME@QcsOdx-ME hydrogel, B is the degradation curves of the AlgOdx-ME hydrogel and the QcsOdx-ME hydrogel in pH 7.4 and pH 5.0 buffers, C is the degradation curve of the AlgOdx-ME@QcsOdx-ME double-layer hydrogel in pH 7.4 and pH 5.0 buffers, and D is the anthocyanin release curve of the AlgOdx-ME@QcsOdx-ME double-layer hydrogel.

[0023] Figure 2 These are the adhesion, tensile, antibacterial and hemostatic performance test results of the AlgOdx-ME@QcsOdx-ME hydrogel in Example 3, wherein A is the adhesion test result of the QcsOdx-ME hydrogel, B is the tensile test result of the QcsOdx-ME hydrogel, C is the antibacterial experiment result, D is the colony forming unit statistical chart of the antibacterial experiment, E is the hemostatic experiment result of the mouse liver bleeding model, and F is the statistical chart of the hemostatic experiment.

[0024] Figure 3 These are the infection monitoring results of the AlgOdx-ME@QcsOdx-ME hydrogel in Example 4, wherein A is the color change result of the mulberry extract solution in the range of pH 4 to pH 10, and B is the infection monitoring result of the AlgOdx-ME@QcsOdx-ME hydrogel in vivo.

[0025] Figure 4 Figure 5 is the wound treatment effect of the AlgOdx-ME@QcsOdx-ME hydrogel in Example 5, wherein A is the macroscopic image of the wound at a specific time point after treatment, B is a statistical graph of the relative wound area, C is the in vivo antibacterial experiment result, D is a statistical graph of the colony forming units of the in vivo antibacterial experiment, E is the immunofluorescence staining result of CD86 of the wound tissue on the 5th day, F is a statistical graph of the average fluorescence intensity of CD86 of the wound tissue, G is the immunofluorescence staining result of CD206 of the wound tissue on the 5th day, and H is a statistical graph of the average fluorescence intensity of CD206 of the wound tissue. DETAILED DESCRIPTION

[0026] Commercially available mulberries can also be used to prepare the double-layer smart hydrogel in the following examples.

[0027] Example 1 Preparation of double-layer smart hydrogel

[0028] (1) Preparation of mulberry extract

[0029] First, 1 kg of commercially available fresh mulberry fruits, accurately weighed, was placed in a 70% ethanol aqueous solution containing 0.1% (v / v) hydrochloric acid and soaked for 4 hours. Subsequently, the mixture obtained by the above soaking was collected, centrifuged at a speed of 4000rpm for 10 minutes by a centrifuge to separate the supernatant containing the target component, and concentrated under reduced pressure at a constant temperature of 30°C. The concentrated solution was introduced into a chromatographic column equipped with AB-8 macroporous resin for static adsorption for 3 hours, with a sample load of 5BV. Distilled water was used as the initial eluent for preliminary elution until the effluent was colorless, and then gradient elution was performed using 5%, 10% and 20% ethanol aqueous solutions with a volume fraction of 5%, 10% and 20%, respectively, with an elution flow rate of 2.0mL / min and an elution volume of 2BV, 3BV and 3BV, respectively. Finally, the solution eluted with 10% and 20% ethanol aqueous solutions was concentrated and freeze-dried to obtain mulberry extract. The total anthocyanin content measured by pH differential method was 72.6%.

[0030] (2) Synthesis of Aldehyde Dextran

[0031] 15 g of dextran was dissolved in 200 mL of deionized water, and then 19 g of sodium periodate (NaIO4) was slowly added, and the mixture was reacted at 25°C in the dark for 6 hours. After the reaction was completed, 2 mL of diethylene glycol was added dropwise to terminate the reaction. Then, the reaction solution was dialyzed in deionized water for 3 days, and finally freeze-dried to obtain aldehyde-modified dextran.

[0032] (3) Synthesis of upper and lower hydrogels

[0033] 0.4g of aldehyde-deoxyglucan and 50mg of mulberry extract were dissolved in 10mL of PBS buffer (pH 7.4) to prepare an aldehyde-deoxyglucan-mulberry extract solution; at the same time, 0.4g of chitosan quaternary ammonium salt (90% substitution, Shanghai Yuanye Biology, item number S26618) and 50mg of mulberry extract were dissolved in 10mL of PBS buffer (pH 7.4) to form a chitosan quaternary ammonium salt-mulberry extract solution. The aldehyde-deoxyglucan-mulberry extract solution and the chitosan quaternary ammonium salt-mulberry extract solution were mixed in a mold at a volume of 1:1, and allowed to stand for 1 minute for cross-linking reaction to form a lower layer hydrogel (AlgOdx-ME). 0.35g of sodium alginate, 0.4g of aldehyde-deoxyglucan and 50mg of mulberry extract were mixed and dissolved in 10mL of PBS buffer (pH 7.4) as the upper layer hydrogel prepolymer solution. Afterwards, the upper hydrogel prepolymer solution was slowly added to the mold, and an equal volume of CaCl2 solution was evenly sprayed and allowed to stand for 20 min to allow the upper hydrogel to be fully cross-linked. The obtained upper hydrogel was named QcsOdx-ME.

[0034] (4) Synthesis of double-layer hydrogel network

[0035] 0.4g of aldehyde-deoxyglucan and 50mg of mulberry extract were dissolved in 10mL of PBS buffer (pH 7.4) to obtain an aldehyde-deoxyglucan-mulberry extract solution; at the same time, 0.4g of chitosan quaternary ammonium salt (90% substitution, Shanghai Yuanye Biology, item number S26618) and 50mg of mulberry extract were dissolved in 10mL of PBS buffer (pH 7.4) to form a chitosan quaternary ammonium salt-mulberry extract solution. Subsequently, 0.35g of sodium alginate, 0.4g of aldehyde-deoxyglucan and 50mg of mulberry extract were mixed and dissolved in 10mL of PBS buffer (pH 7.4) as the upper hydrogel prepolymer solution. The aldehyde-deoxyglucan-mulberry extract solution and the chitosan quaternary ammonium salt-mulberry extract solution were mixed in a mold at a volume ratio of 1:1, and allowed to stand for 1 minute for cross-linking reaction to form a lower hydrogel. After that, the upper hydrogel prepolymer solution was slowly added to the lower hydrogel, and the CaCl2 solution was evenly sprayed and allowed to stand for 20 minutes to allow the upper hydrogel to be fully cross-linked. Through the above steps, a cross-linked hydrogel (AlgOdx-ME@QcsOdx-ME) with a double-layer structure was successfully prepared.

[0036] Example 2 Characterization of double-layer smart hydrogel

[0037] (1) The AlgOdx-ME@QcsOdx-ME hydrogel sample was quickly immersed in liquid nitrogen to achieve instant freezing, and then it was broken into two parts and freeze-dried separately. After the sample surface was gold-sprayed, the microstructure of the double-layer hydrogel was observed and analyzed using a scanning electron microscope (SEM; model: GeminiSEM 300, manufacturer: Zeiss). The results are shown in Figure 2. Figure 1 -A. Figure 1 -A shows that the average pore size of the upper hydrogel is 12.65 μm, and the average pore size of the lower hydrogel is 14.98 μm. The upper and lower layers of the AlgOdx-ME@QcsOdx-ME hydrogel are interconnected porous network structures, which is conducive to the exchange of substances between the hydrogel and the wound.

[0038] (2) Two groups of hydrogels, AlgOdx-ME and QcsOdx-ME, were set up. The initial mass (W0) of the freeze-dried hydrogel was measured in each group. Subsequently, each group of samples was immersed in 8 mL of PBS solution (pH values ​​were 7.4 and 5.0, respectively) and placed in a constant temperature oscillator at a stable temperature of 37°C and a rotation speed of 100 rpm. The experimental period was two weeks, during which samples were taken out every two days for freeze-drying, and the mass of the remaining hydrogel (W0) was recorded. t The hydrogel degradation rate is calculated according to the following formula: Remaining weight percentage (%) = (W t / W0)×100%, the result is as follows Figure 1 -B. Figure 1 -B shows that the degradation rates of AlgOdx-ME under weakly alkaline and acidic conditions are similar, while under pH 5.0 conditions, QcsOdx-ME is completely degraded on the 8th day, and the degradation rate is significantly faster than that under pH 7.4 conditions.

[0039] (3) The AlgOdx-ME@QcsOdx-ME hydrogel with an initial mass of W0 was immersed in 8 mL of PBS solution (pH values ​​were 7.4 and 5.0, respectively) and placed in a constant temperature oscillator set at 37°C and 100 rpm. The experimental period was two weeks, during which samples were taken out every two days for freeze-drying, and the mass of the remaining hydrogel (W0) was recorded. t The hydrogel degradation rate is calculated according to the following formula: Remaining weight percentage (%) = (W t / W0)×100%, the result is as follows Figure 1 -C. Figure 1 -C shows that the degradation rate of AlgOdx-ME@QcsOdx-ME hydrogel at pH 5.0 is significantly faster than that at pH 7.4.

[0040] (4) 500 μL of the double-layer hydrogel sample was placed in 8 mL of PBS solution with different pH values ​​(7.4 or 5.0). 600 μL of the solution was removed every two days and an equal amount of fresh PBS was added to maintain a constant volume of the solution. According to the Lambert-Beer law, a standard curve was constructed in advance using anthocyanin standards, and then the concentration of anthocyanins in the solution taken out at each time point was determined using this curve. The results are shown in Figure 1 -D. Figure 1 -D shows that the release rate of anthocyanins from AlgOdx-ME@QcsOdx-ME hydrogel at pH 5.0 is faster than that at pH 7.4.

[0041] Example 3 Performance test of hydrogel

[0042] (1) QcsOdx-ME is the main part of the lower layer hydrogel that is widely in contact with the wound tissue. Therefore, independent adhesion and tensile performance evaluation experiments were conducted on QcsOdx-ME. The results are as follows: Figure 2 -A~ Figure 2 -B. Figure 2 -A~ Figure 2 -B shows that QcsOdx-ME has good adhesion properties and also good tensile properties, and is suitable for wounds with a larger range of motion.

[0043] (2) The antibacterial efficacy of AlgOdx-ME@QcsOdx-ME was evaluated by plate colony counting method. First, 1 mL of Staphylococcus aureus suspension containing 106 CFU / mL was mixed with 200 μL of PBS buffer (pH 7.4) or hydrogel and co-cultured at 37°C for 2 hours. Subsequently, 10 μL of the mixture was diluted to 1 mL, and 10 μL of the dilution was evenly spread on a Luria-Bertani (LB) agar plate and cultured at 37°C for 18 hours. Finally, the number of colony forming units (CFU) was counted and the antibacterial rate was calculated based on this. The results are shown in Figure 2. Figure 2 -C~ Figure 2 -D. Figure 2 -C~ Figure 2 -D shows that AlgOdx-ME@QcsOdx-ME has a strong antibacterial effect, killing more than 95% of Staphylococcus aureus.

[0044] (3) The hemostatic properties of the hydrogel were evaluated using a liver bleeding model. After the mice were anesthetized with an intraperitoneal injection of sodium pentobarbital, the abdominal skin was cut to expose the liver, and then a pre-weighed filter paper (W0) was placed under the liver. The liver was punctured with an 18G needle to induce bleeding, and then the hydrogel was immediately applied to the liver wound, while the control group did not receive any treatment. Photos were taken and the weight of the filter paper (W0) was measured at 60 seconds. t ) Calculate blood loss (mg) according to the following formula = W t -W0, the result is as follows Figure 2 -E~ Figure 2 -F. Figure 2 -E~ Figure 2 -F shows that AlgOdx-ME@QcsOdx-ME hydrogel has a significant hemostatic effect.

[0045] Example 4 In vivo infection monitoring function

[0046] (1) In order to evaluate the ability of mulberry extract to detect pH, PBS solutions containing mulberry extract (5 mg / mL) were prepared and adjusted to the specified pH range (4.0-10.0). Photos were taken to record the color of the mulberry extract solutions under different pH conditions. The results are shown in Figure 2. Figure 3 -A. Figure 3 -A shows that the color of the mulberry extract solution is lavender under neutral conditions, orange under pH 6.0, pink and red under pH 5.0 and 4.0, respectively. In an alkaline environment, the mulberry extract solution shows gray-blue, dark green and yellow-brown under pH 8.0, pH 9.0 and pH 10.0, respectively.

[0047] (2) To evaluate the pH indicator effect of the upper AlgOdx-ME hydrogel, 500 μl of AlgOdx-ME hydrogel and 5 ml of buffer solutions with different pH values ​​(pH range 4-10) were added to a 12-well plate and incubated for 1 hour, and then the hydrogel was taken out and photographed. The results showed that the hydrogel showed the same color change trend as the mulberry extract solution in the buffer solution with a pH range of 4-10.

[0048] (3) Rats were anesthetized by intraperitoneal injection of sodium pentobarbital solution, and then the back hair was shaved. Two full-thickness skin wounds were made on the back of the rats with a 15-mm round-hole punch needle, and then 100 μL of Staphylococcus aureus suspension (2×10 8 CFU / ml) to induce wound infection and obtain an infected wound model. The wound without the injection of Staphylococcus aureus suspension was used as an uninfected wound. The pH value changes before and after wound infection were measured by a wide range of pH test strips. The results showed that the pH value of the wound after skin injury was 7.0-8.0, while the pH value of the wound on the first and second days after wound infection was about 5.0.

[0049] (4) For the infected wound model, the hydrogel was first applied after wound modeling and a photo was taken 1 hour later. Then, the hydrogel was removed and 100 μL of Staphylococcus aureus suspension (2×10 8 CFU / ml) to induce wound infection. 24 hours after wound modeling, AlgOdx-ME@QcsOdx-ME hydrogel was applied to the wound again, and photos were taken 48 hours after wound modeling. At the same time, an uninfected rat wound model was constructed, and then AlgOdx-ME@QcsOdx-ME was applied. Photos were taken 1 hour and 48 hours after application to record the color change of the hydrogel as a control. The results are shown in Figure 3 -B. Figure 3 -B shows that: in uninfected wounds, AlgOdx-ME@QcsOdx-ME appears blue-purple on both days 0 and 2, indicating that the wound pH is between 7.0 and 8.0. Once applied to infected wounds, AlgOdx-ME@QcsOdx-ME hydrogel will change from blue-purple to pink, and is therefore used to monitor wound infection.

[0050] Example 5 In vivo therapeutic effect

[0051] (1) For infected wounds, PBS buffer (pH 7.4), AlgOdx-ME and AlgOdx-ME@QcsOdx-ME were applied, respectively, where AlgOdx-ME was used as a control of non-microenvironment responsive hydrogel. Wound photos were taken on days 0, 3, 7 and 14, and the wound area was measured using Image J software. The wound area was expressed as a relative percentage, and the calculation formula was: Relative wound area (%) = (S t / S0)×100%, where S t is the wound area at each time point, S0 is the wound area on day 0, and the results are as follows Figure 4 -A~ Figure 4 -B. Figure 4 -A~ Figure 4 -B shows that the healing speed of infected wounds after treatment with AlgOdx-ME@QcsOdx-ME is faster than that after treatment with AlgOdx-ME and PBS buffer (pH 7.4), indicating that AlgOdx-ME@QcsOdx-ME with pH-responsive drug release properties has a stronger effect in promoting wound healing.

[0052] (2) To evaluate the antibacterial efficacy of the hydrogel in vivo, wound bacterial samples were collected on the third day of the experiment for culture, and the colony count was quantified by the plate colony counting method. The results are shown in Figure 4 -C~ Figure 4 -D. Figure 4 -C~ Figure 4 -D shows that AlgOdx-ME@QcsOdx-ME exhibits significant wound bacteria clearance effect.

[0053] (3) On the 5th day, the experimental rats were euthanized and wound tissue samples were collected. Subsequently, the wound tissues were fixed with 4% paraformaldehyde, and after a gradient alcohol step, the tissues were embedded in paraffin and sliced ​​for later use.

[0054] (4) The tissue was immunostained with CD86 antibody, and then the cell nuclei in the tissue were stained with DAPI. The tissue staining results were photographed with a fluorescence microscope. The results are shown in Figure 4. Figure 4 -E~ Figure 4 -F. Figure 4 -E~ Figure 4 -F shows that: on the 5th day, the CD86 expression in the wound after AlgOdx-ME@QcsOdx-ME hydrogel treatment was lower than that in the PBS treatment group and the AlgOdx-ME hydrogel treatment group, indicating that AlgOdx-ME@QcsOdx-ME hydrogel has the effect of inhibiting the polarization of macrophages M1.

[0055] (5) CD206 antibody was used to perform immunofluorescence staining on the tissue, and then DAPI was used to stain the cell nuclei in the tissue. The tissue staining results were photographed using a fluorescence microscope. The results are shown in Figure 5. Figure 4 -G~ Figure 4 -H. Figure 4 -G~ Figure 4 -H shows that: on the 5th day, the expression of CD206 in the wound after AlgOdx-ME@QcsOdx-ME hydrogel treatment was higher than that in the PBS treatment group and the AlgOdx-ME hydrogel treatment group, indicating that AlgOdx-ME@QcsOdx-ME hydrogel has the effect of promoting the M2 polarization of macrophages.

[0056] (6) After completing the in vivo wound healing evaluation, the rat heart, liver, spleen, lung and kidney were collected, and the wound tissue was fixed with 4% paraformaldehyde. After a gradient alcohol step, the tissue was embedded in paraffin and sliced. The above slices were stained with hematoxylin-eosin, and the tissue staining results were photographed with a fluorescence microscope. The results showed that AlgOdx-ME@QcsOdx-ME hydrogel treatment did not cause pathological changes in the main organs of rats, indicating that AlgOdx-ME@QcsOdx-ME hydrogel is biosafe.

[0057] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a double-layer hydrogel for wound repair and infection monitoring, characterized in that: The preparation method comprises the following steps: (1) dissolving 0.3-0.5 g of aldehyde-deoxyglucan and 45-55 mg of mulberry extract in 8-12 mL of PBS buffer at pH 7.4 to prepare an aldehyde-deoxyglucan-mulberry extract solution; (2) dissolving 0.3-0.5 g of chitosan quaternary ammonium salt and 45-55 mg of mulberry extract in 8-12 mL of PBS buffer at a pH of 7.4 to form a chitosan quaternary ammonium salt-mulberry extract solution; (3) 0.3-0.4 g of sodium alginate, 0.3-0.5 g of aldehyded dextran and 45-55 mg of mulberry extract were mixed and dissolved in 8-12 mL of PBS buffer with a pH of 7.4 to serve as the upper hydrogel prepolymer solution; (4) mixing the aldehyde-deoxyglucan-mulberry extract solution and the chitosan quaternary ammonium salt-mulberry extract solution in a volume ratio of 1-2:1-2, and allowing to stand for a cross-linking reaction to form a lower layer of hydrogel; (5) Add the upper hydrogel prepolymer solution on top of the lower hydrogel, spray the metal cation salt solution, and let it stand to allow the upper hydrogel to be fully cross-linked, thereby obtaining a cross-linked hydrogel AlgOdx-ME@QcsOdx-ME with a double-layer structure.

2. The preparation method according to claim 1, characterized in that: In the step (1), the amount of aldehyde-deoxyglucan used is 0.4 g, and the amount of mulberry extract used is 50 mg.

3. The preparation method according to claim 2, characterized in that: In the step (2), the amount of chitosan quaternary ammonium salt used is 0.4 g, and the amount of mulberry extract used is 50 mg.

4. The preparation method according to claim 3, characterized in that: In the step (3), the amount of sodium alginate used is 0.35 g, the amount of formaldehyded dextran used is 0.4 g, and the amount of mulberry extract used is 50 mg.

5. The preparation method according to claim 4, characterized in that: The metal cation salt solution in step (5) is any one of calcium, copper and zinc salt solutions.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The volume of PBS buffer in steps (1)-(3) is 10 mL.

7. A double-layer hydrogel prepared by the preparation method according to any one of claims 1 to 5.

8. A double-layer hydrogel prepared by the preparation method according to claim 6.

9. Use of the double-layer hydrogel according to claim 7 in preparing wound repair and infection monitoring products.

10. Use of the double-layer hydrogel according to claim 8 in preparing wound repair and infection monitoring products.

Citation Information

Patent Citations

  • Coordination compound as well as preparation method and application thereof

    CN113788871A

  • Wound dressing and preparation method thereof

    CN116920154A

Cited By

  • Hydrogel dressing with double response characteristics as well as preparation method and application of hydrogel dressing

    CN119950804A

  • A hydrogel dressing with dual-response properties, its preparation method, and its application.

    CN119950804B

  • Visual hydrogel based on multiple response mechanisms and preparation method and application thereof

    CN120132039A

  • Visual hydrogel based on multiple response mechanism and preparation method and application thereof

    CN120132039B